Language Functions Used by The Main Characters of The Marriage Story Movie - Shely Martha Sanastia; Mytha Candria (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2022)
People use different utterances by considering the social context in which communication  takes place. An utterance may have more than one meaning and function depending on social  context and other factors. This study aims to describe the spoken language functions of the main  characters, Charlie and Nicole, in the Marriage Story movie. This descriptive qualitative research  used Roman Jacobson’s language function classification to categorize the selected utterances  found in Marriage Story movie into one of the six functions (emotive, conative, referential,  metalingual, phatic, and poetic). To interpret the classified data and the contexts or situations, I  relate the language functions to social factors and social dimensions based on Holmes’  categorization. The results show that all six language functions appeared in Nicole and Charlie’s  utterances. The data analysis depicts that emotive function is predominantly used by the main  characters throughout the whole movie. Moreover, those language functions are influenced by  social factors and social dimensions.Keywords: language function; social factor; social dimension; Marriage Story.